Assessing wetland health using a newly developed land cover citizen science tool for use by local people who are not wetland specialists - Nondumiso Dumakude; Mark Graham (Environmental Association of Southern Africa, 2017)
More than half of the wetlands in South Africa have been degraded or lost due to economic activities, urban developments and poor wetland management. Reversing the trend would require the participation of a wide range of actors in addition to scientists. A case has been made for a citizen science approach in order to empower the public with skills and knowledge that would enable them to understand environmental issues without depending on specialists. However, the wetland health assessment tools used in South Africa are highly technical, rendering them largely inaccessible to non-specialists. Recently, Kotze (2015) developed a tool which seeks to address this gap by involving the wider community in monitoring the health of wetlands in South Africa. The aim of the present study was to test the extent to which the new wetland health tool can be used by local people to better understand their surrounding wetlands. The study's findings indicated that the tool enabled non-specialists to generate information about wetlands that was not significantly different from that produced by specialists.